하악골 결손의 재건을 위한 혈행화된 비골 이식술에서의 장기간의 체적변화 - 김윤태(Yoon-Tae Kim); 전승호(Seung-Ho Jeon); 염학렬(Hak-Ryol Yeom); 안강민(Kang-Min Ahn); 명훈(Hoon Myoung); 황순정(Soon-Jung Hwang); 서병무(Byoung-Moo Seo); 최진영(Jin-Young Choi); 정필훈(Pill-Hoon Choung); 김명진(Myung-Jin Kim); 이종호(Jong-Ho Lee) (Journal of the Korean Association of Oral and Maxillofacial Surgeons, 2006)
Introduction : In recent years, vascularized, i.e., living bone grafts, have been widely applied in the field of oral and maxillofacial surgery, as a method of treatment of congenital or acquired non-unions, and a large defects in mandible. The vascularized fibular graft has been especially used for this purpose because of its shape and mechanical strength. The postoperative hypertrophy of grafted fibula is of particular interest to us. Material and methods : This study was undertaken to determine the volume change(indirect methods) and radiographic appearance of a free vascularized fibular graft as it responds to the mechanical and physiologic features of its new environment. In order to elucidate the long term effect on fibular mass after mandibular reconstruction, change in various method of volume change was utilized as indirect measure of change in long-term. Results : The younger the patient, the more prominent and rapid the hypertrophy of the graft. the hypertrophy of the graft never exceeded the diameter of the recipient bone, except for callus enlargement after stress fracture of the grafted bone. Conclusion : Etiologic explanations for this phenomenon have not been clarified in the previeous literature. some of the factors implicated include a periosteal reaction or new bone formation, as seen at the onset of bone union after a fracture in a child, a reaction to the mechanical loading on the graft and a reaction to the circulatory changes resulting from the grafting procedure. KCI Citation Count: 1